The Influence of Self-Efficacy And Motivation on Interest in Reporting National Quality Indicators Through Healthcare Facility Registration Interest - Zahro, Siti Lailatus; Indasah, Indasah; Wardani, Ratna (GLOBAL HEALTH SCIENCE GROUP, 2025)
The lack of interest of independent medical practice healthcare facilities and independent dentist practice healthcare facilities in registering health facilities and reporting national quality indicators (national quality indicators) as a condition for accreditation will affect the quality of health facilities so that self-efficacy and motivation are really needed to increase this interest. The aim of this research is to analyze the influence of self efficacy and motivation on national quality indicators reporting interest through health facility registration interest as an intervening variable (study on independent medical practice healthcare facilities and independent dentist practice healthcare facilities in the kediri regency area). The research design used was analytical observational with a